PENGARUH MORAL PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI BANDUNG RAYA - Rizki Indrawan; Anissa Yuniar Larasati (FEBI UIN Sunan Gunung Djati Bandung, 2022)
This study aims to analyze the effect of tax morale on MSME taxpayer compliance in Greater Bandung. Tax morale can help overcome the problem of tax compliance, where this can be seen at a high level of tax compliance with a very low level of prevention. The population used in this research is UMKM WP spread throughout Greater Bandung. The sample used by taxpayers who do business in Cimahi City, Bandung City, West Bandung Regency and Bandung Regency. Analysis using Logistic Regression Analysis. Descriptive research method with a qualitative approach. Research data comes from primary data by distributing questionnaires. The results of the study show that tax morale which consists of the environment, institutional perceptions and ethics does not partially influence MSME taxpayer compliance in paying taxes. Simultaneously it shows that it has a significant influence on MSME tax compliance in fulfilling its tax obligations.